2020
DOI: 10.3390/nano10020291
|View full text |Cite
|
Sign up to set email alerts
|

PMMA Thin Film with Embedded Carbon Quantum Dots for Post-Fabrication Improvement of Light Harvesting in Perovskite Solar Cells

Abstract: Perovskite solar cells (PSCs) with a standard sandwich structure suffer from optical transmission losses due to the substrate and its active layers. Developing strategies for compensating for the losses in light harvesting is of significant importance to achieving a further enhancement in device efficiencies. In this work, the down-conversion effect of carbon quantum dots (CQDs) was employed to convert the UV fraction of the incident light into visible light. For this, thin films of poly(methyl methacrylate) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 10 publications
1
34
0
Order By: Relevance
“…Poly(methyl methacrylate) (PMMA) was also often used as a matrix for the fabrication of CD-based luminescent films and for fabrication of LEDs and WLEDs [ 9 , 55 ]. In [ 26 ], light-harvesting properties of perovskite solar cells with CDs dispersed in the PMMA layer were improved through the down-conversion effect ( Figure 2 b). In the electroluminescent LED, PMMA can play a role of an isolating layer, which helps to restrain the electron injection from an active CD-containing layer to the hole transport layer, and prevent charge recombination at the anode [ 92 ].…”
Section: Improvements Of Optical Properties Of Cdsmentioning
confidence: 99%
See 2 more Smart Citations
“…Poly(methyl methacrylate) (PMMA) was also often used as a matrix for the fabrication of CD-based luminescent films and for fabrication of LEDs and WLEDs [ 9 , 55 ]. In [ 26 ], light-harvesting properties of perovskite solar cells with CDs dispersed in the PMMA layer were improved through the down-conversion effect ( Figure 2 b). In the electroluminescent LED, PMMA can play a role of an isolating layer, which helps to restrain the electron injection from an active CD-containing layer to the hole transport layer, and prevent charge recombination at the anode [ 92 ].…”
Section: Improvements Of Optical Properties Of Cdsmentioning
confidence: 99%
“…( b ) Schematics of perovskite solar cells without (left) and with (right) light harvesting PMMA layer with embedded CDs. Reprinted with permission from reference [ 26 ]. ( c ) Photographs (taken under daylight and UV excitation) of green- and red-emissive CDs in solution and those embedded into MTES or APTES matrices to form CD-based glasses for trichromatic white light emitting diodes (WLEDs).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…In general, five major areas are being investigated to come up with possible solutions for the problems mentioned above. They include (i) perovskite composition and crystal structure (Luo and Daoud, 2016;Mitchell et al, 2017), (ii) engineering of perovskite growth methods (Ng et al, 2015(Ng et al, , 2018Babayigit et al, 2018;Shen et al, 2018;Hu et al, 2020a), (iii) optimization of carrier transport materials and interfaces (Liu et al, 2017;Hu et al, 2020b,c;Wang et al, 2021), (iv) device architectures (Hanmandlu et al, 2018;Ren et al, 2018;Maxim et al, 2020;Shalenov et al, 2020), and (v) encapsulation (Dong et al, 2016;Fu et al, 2019;Emami et al, 2020). Some comprehensive review papers on those topics have also been published (Jiang et al, 2018;Sajid et al, 2018;Ouyang et al, 2019;Hanmandlu et al, 2020;Hu et al, 2020a;Zhou et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Three research works [ 1 , 2 , 3 ] reported recent emerging materials, including 2D Bi 2 Se 3 in optoelectronic applications, and discussed fundamental behaviors of dyes in confined media. Another research work reported by Maxim et al [ 4 ] explores the enhancement of light harnessing in perovskite solar cells with embedded carbon quantum dots. Most of the articles are focused on photocatalytic solar fuel generation.…”
mentioning
confidence: 99%